2013
DOI: 10.1002/ajmg.a.36210
|View full text |Cite
|
Sign up to set email alerts
|

Co‐occurrence of hemiscrotal agenesis with cutis marmorata telangiectatica congenita and hydronephrosis affecting the same side of the body

Abstract: To our knowledge, there are nine previous reports of patients with congenital scrotal agenesis (CSA), seven of which were bilateral, and unilateral in two, also named as hemiscrotal agenesis (HSA). Here, we report a male infant with the previously undescribed co-occurrence of HSA with cutis marmorata telangiectatica congenita (CMTC), and hydronephrosis due to vesicoureteral reflux, all of them on the left side. CMTC is a segmental vascular malformation usually attributed to mosaicism of a postzygotic mutation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Mohan et al ., based on two cases of complete scrotal agenesis after treatment with topical testosterone therapy, suggested that the presence of remnants of the LSF with intact androgen receptors could potentially result from a localized 5α‐reductase type 2 deficiency with enough dihydrotestosterone to prevent labia formation, but not enough to stimulate scrotal development . Corona‐Rivera et al ., in a case of hemiscrotal agenesis, suggested a localized 5α‐reductase type 2 deficiency was unlikely and that their patient had androgen insensitivity, confined to the LSF . Although the expression of these genes was only mentioned in previous reports of scrotal agenesis, we showed in the present case that scrotal skin with absent rugae and pigmentation has low activity against androgen owing to the low expression of AR and SRD5A2 .…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Mohan et al ., based on two cases of complete scrotal agenesis after treatment with topical testosterone therapy, suggested that the presence of remnants of the LSF with intact androgen receptors could potentially result from a localized 5α‐reductase type 2 deficiency with enough dihydrotestosterone to prevent labia formation, but not enough to stimulate scrotal development . Corona‐Rivera et al ., in a case of hemiscrotal agenesis, suggested a localized 5α‐reductase type 2 deficiency was unlikely and that their patient had androgen insensitivity, confined to the LSF . Although the expression of these genes was only mentioned in previous reports of scrotal agenesis, we showed in the present case that scrotal skin with absent rugae and pigmentation has low activity against androgen owing to the low expression of AR and SRD5A2 .…”
Section: Discussionsupporting
confidence: 41%
“…Congenital scrotal agenesis is the rarest anomaly in scrotal development disorders, and it is characterized by the absence of scrotal rugae in the perineum between the penis and anus . In previous case reports, seven patients had bilateral scrotal agenesis, which was named complete scrotal agenesis, and three patients had unilateral scrotal agenesis, which was named hemiscrotal agenesis . However, the pathogenesis and clinical manifestations remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital scrotal agenesis (CSA) is a rare malformation characterized by the absence of scrotal skin, and has been previously described as a bilateral or unilateral defect in seven and four patients, respectively . From these, CSA has been part of a different pattern of defects or syndromes in six out of 11 patients, supporting the existence of genetic heterogeneity in this anomaly .…”
mentioning
confidence: 99%
“…Congenital scrotal agenesis (CSA) is a rare malformation characterized by the absence of scrotal skin, and has been previously described as a bilateral or unilateral defect in seven and four patients, respectively . From these, CSA has been part of a different pattern of defects or syndromes in six out of 11 patients, supporting the existence of genetic heterogeneity in this anomaly . As the scrotum is formed by fusion of the labioscrotal folds (LSF) under androgen action, CSA it has been proposed as a primary failure of the LSF development or as a secondary consequence of a localized steroid‐5‐alpha‐reductase, alpha polypeptide 2 (SRD5A2) deficiency, or androgen insensitivity, affecting either both LSF in complete CSA .…”
mentioning
confidence: 99%
See 1 more Smart Citation